78. Longitudinal Analysis of T cells in COVID-19 Survivors with Post-Acute Sequelae of COVID-19 Reveals Associations between Individual Symptoms and Inflammatory Indexes. (15th December 2022) - LaVergne, Stephanie; LaVergne, Stephanie; Dutt, Taru; McFann, Kim; Baxter, Bridget; Webb, Tracy; Berry, Kailey; Stomberg, Sophia; Dunn, Julie; Henao-Tamayo, Marcela; Ryan, Elizabeth
Abstract: Background: Many individuals infected with SARS-CoV-2 are left with persistent symptoms of COVID-19. Post-acute sequelae of COVID-19 (PASC) can affect quality of life and functionality. The mechanism underlying PASC is unknown but elevated inflammatory markers several months post infection have been found in those with PASC. Methods: Individuals diagnosed with COVID-19 were evaluated longitudinally for PASC and persistent symptoms. CD4 + and CD8 + cellular markers and intracellular cytokines were assessed at each follow-up time point and analyzed by individual PASC symptoms reported. Results: Participants who reported persistent dyspnea, forgetfulness, confusion, and chest pain had significantly higher levels of CD8 + Ki67 + cells. Those with dyspnea also had significantly higher levels of CD8 + CD38 +, CD8 + Granzyme B +, and CD8 + IL10 + cells. Those who suffered from forgetfulness, chest pain, and joint pain had significantly higher levels of CD4 + CD25 + cells. Table 1 Baseline participant characteristics and demographic data. Figure 1 Differences in CD8 T cell markers and inflammatory cytokines in participants reporting symptoms of: a) dyspnea (N=20) and without dyspnea (N=104), b) fatigue (N=35) and without fatigue (N=89), c) confusion (N=17) and without confusion (N=107), d) difficulty concentrating (DC) (N=26) and without difficulty concentrating (N= 98), and e) forgetfulness or absent-mindedness (N=28) and without forgetfulness or absent-mindedness (N=96). *p<0.05. Figure 2 Inflammatory indexes measured at 15–44, 45–89, 90–174, and > 175 days post PCR by symptom: A) dyspnea B) fatigue C) confusion D) DC=difficulty concentrating E) forgetfulness. Conclusion: These findings suggest continued CD8 + T cell and CD4+CD25 + T cell activation and response following SARS-CoV-2 infection in patients with PASC. An increase in T regulatory cells suggests an ongoing attempt to control host inflammation in a subset of these patients. These results shed further light on continued immune system activation and chronic inflammation as a link to symptoms in COVID-19 survivors suffering from PASC. Disclosures: All Authors : No reported disclosures.